Menjaga Keaslian Brand pada Brand Authenticity dengan Menggunakan Metode The Planned Behaviour - Kurniawati; Yolanda Masnita; Arnandi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to deepen knowledge about the importance of the concept of Social Media Marketing towards Brand Authenticity, as well as to build hypotheses related to consumer potential and managerial implications for marketing. Through an in-depth study of various existing literature, it can be concluded that Social Media Marketing have significant impact to Brand Authenticity. Objectives - This study aims to highlight the mediating role of Value Co-Creation between Social Media Marketing (eWOM, Trendiness, Social Support) and Brand Authenticity. The study conducted a survey of the general public with respondents who use social media such as Instagram, TikTok, Facebook and Twitter with a sample size of 302 using Google Form and Structural Equation Modeling (SEM) to test the relationship hypothesis in the proposed model